Otoferlin Is Required for Proper Synapse Maturation and for Maintenance of Inner and Outer Hair Cells in Mouse Models for DFNB9 - Stalmann, Ursula; Franke, Albert Justin; Al-Moyed, Hanan; Strenzke, Nicola; Reisinger, Ellen (Frontiers in Cellular Neuroscience, 2021)
Deficiency of otoferlin causes profound prelingual deafness in humans and animal models. Here, we closely analyzed developmental deficits and degenerative mechanisms in Otof knock-out (Otof-/-) mice over the course of 48 weeks. We found otoferlin to be required for proper synapse development in the immature rodent cochlea: In absence of otoferlin, synaptic pruning was delayed, and postsynaptic boutons appeared enlarged at two weeks of age. At postnatal day 14 (P14), we found on average ~15 synapses per inner hair cell (IHC) in Otof-/- cochleae as well as in wild-type controls. Further on, the number of synapses in Otof-/- IHCs was reduced to ~7 at 8 weeks of age and to ~6 at 48 weeks of age. In the same period, the number of spiral ganglion neurons (SGNs) declined in Otof-/- animals. Importantly, we found an age-progressive loss of IHCs to an overall number of 75% of wildtype IHCs. The IHC loss more prominently but not exclusively affected the basal aspects of the cochlea. For outer hair cells (OHCs), we observed slightly accelerated age-dependent degeneration from base to apex. This was associated with a progressive decay in DPOAE amplitudes for high frequency stimuli, which could first be observed at the age of 24 weeks in Otof-/- mice. Our data will help to plan and predict the outcome of a gene therapy applied at various ages of DFNB9 patients.